If you simplify x • 5x by multiplying like terms, your answer is 5 times x raised to some exponent. What is the exponent of x?

Question

Asked 1/17/2013 7:57:08 AM

Updated 6/8/2014 4:43:19 PM

2 Answers/Comments

s

andrewpallarca|Points 18626|

Expert answered|may100|Points 2110|

Expert answered|fyticue|Points 0|

Question

Asked 1/17/2013 7:57:08 AM

Updated 6/8/2014 4:43:19 PM

2 Answers/Comments

Rating

3

The degree of the polynomial 2x^3 - 3x^2 + 4x + 5 is 3.

Added 6/8/2014 4:41:38 PM

This answer has been confirmed as correct and helpful.

3

2x^3 - 3x^2 + 4x + 5, when x = 4:

2(4)^3 - 3(4)^2 + 4(4) + 5

= 2(64) - 3(16) + 16 + 5

= 128 - 48 + 21

= 80 + 21

= 101

2(4)^3 - 3(4)^2 + 4(4) + 5

= 2(64) - 3(16) + 16 + 5

= 128 - 48 + 21

= 80 + 21

= 101

Added 6/8/2014 4:43:19 PM

This answer has been confirmed as correct and helpful.

4x^2 • –3x^3=
**Weegy:** (More)

Question

Not Answered

Updated 4/6/2014 3:02:10 PM

1 Answer/Comment

4x^2 • –3x^3

= -12x^5

= -12x^5

Added 4/6/2014 3:02:10 PM

This answer has been confirmed as correct and helpful.

Multiply these exponents: 4x^2 • –3x^3=
**Weegy:** The answer is 4x^2 • –3x^3= -12 x^5 (More)

Question

Expert Answered

Asked 1/16/2013 9:02:19 AM

0 Answers/Comments

Multiply these binomials: (6x + 7)(20x – 9)=
**Weegy:** (6x + 7)(20x ? 9) = 120x^2 + 86x - 63. **User:** Multiply these binomials: (10x – 11)(–14x + 9)
**Weegy:** (10x ? 11)(?14x + 9) = -140x^2 + 244x - 99. **User:** Multiply these binomials: (16x + 13)(–8x + 15)=
**Weegy:** (16x ? 19)(8x ? 8) = 128x^2 - 280x + 152. **User:** Multiply these binomials: (6x – 3)(–5x + 2)=
**Weegy:** x=-1 and x=-1/5 for the equation 5x^2+6x=-1 **User:** Multiply these binomials: (18x + 20)(–12x – 6)=
(More)

Question

Not Answered

Updated 6/3/2014 11:28:58 PM

5 Answers/Comments

(6x + 7)(20x – 9)

= 120x^2 - 54x + 140x - 63

= 120x^2 + 86x - 63

= 120x^2 - 54x + 140x - 63

= 120x^2 + 86x - 63

Added 6/3/2014 11:22:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/20/2014 1:24:38 PM]

(10x – 11)(–14x + 9)

= -140x^2 + 90x + 154x - 99

= -140x^2 + 244x - 99

= -140x^2 + 90x + 154x - 99

= -140x^2 + 244x - 99

Added 6/3/2014 11:23:39 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/20/2014 1:25:00 PM]

(16x + 13)(–8x + 15)

= -128x^2 + 240x - 104x + 195

= -128x^2 + 136x + 195

= -128x^2 + 240x - 104x + 195

= -128x^2 + 136x + 195

Added 6/3/2014 11:25:13 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/20/2014 1:27:40 PM]

(6x – 3)(–5x + 2)

= -30x^2 + 12x + 15x - 6

= -30x^2 + 27x - 6

= -30x^2 + 12x + 15x - 6

= -30x^2 + 27x - 6

Added 6/3/2014 11:26:56 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/20/2014 1:27:51 PM]

(18x + 20)(–12x – 6)

= -216x^2 - 108x - 240x - 120

= -216x^2 - 348x - 120

= -216x^2 - 108x - 240x - 120

= -216x^2 - 348x - 120

Added 6/3/2014 11:28:58 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/20/2014 1:29:04 PM]

Multiply these binomials: (16x – 19)(8x – 8)=
**Weegy:** (16x – 19)(8x – 8)= = 128x^2 - 280x + 152. **User:** Multiply these binomials: (8x + 11)(–3x + 6)
**Weegy:** (8x + 11)(–3x + 6) = -24x^2 + 15x + 66 **User:** Multiply these binomials: (10x – 11)(–14x + 9)
**Weegy:** (10x – 11)(–14x + 9) = -140x^2 + 244x - 99 (More)

Question

Expert Answered

Updated 6/16/2014 4:46:20 PM

0 Answers/Comments

Multiply: –6x^6 • –2x^4
**Weegy:** -6x^6 • –2x^4 = 12x^10 (More)

Question

Expert Answered

Updated 9/17/2018 6:49:00 PM

0 Answers/Comments

31,900,048

questions answered

There are no comments.